INTESTINAL SPONGES, CAUSES, SYMPTOMS AND TREATMENTS - Shavkatov Rafiq; L. A,Butayev (Western European Studies, 2025)
Intestinal sponges (adgesia) are a condition accompanied by the formation of pathological fibrous compounds in the abdomen or between the intestines, which limit bowel movements and can lead to various degrees of intestinal obstruction
Keywords: symptoms of intestinal sponges; intestinal adhesions; intestinal obstruction